Intranasal immunization with a Bucl8-based vaccine ameliorates bacterial burden and pathological inflammation, and promotes an IgG2a/b dominant response in an outbred mouse model of Burkholderia infection - Grund, Megan; Choi, Soo Jeon; Powell, Lillie; Lukomski, Slawomir (Frontiers in Immunology, 2023)
Burkholderia pseudomallei is a gram-negative bacterium that is the etiological agent of the tropical disease melioidosis. Currently, there is no licensed vaccine for melioidosis, but numerous candidates are being tested for protective efficacy and characterization of the elicited immune response. Our lab has previously reported the immunogenicity of a Bucl8-protein-based peptide antigen, designated L1-CRM197 (Cross-reacting material 197). When given subcutaneously, this vaccine formulation promoted a strong Th2 (IgG1) antibody response, however immunization did not protect from death. In this study, we hypothesized that an intranasally administered L1-CRM197 vaccine would induce protective mucosal immunity. To evaluate vaccine efficacy, we developed a surrogate Burkholderia infection model that employs outbred CD-1 mice which imitates the immunogenetic diversity of humans. Mice were immunized with either L1-CRM197 adjuvanted with fluorinated cyclic diguanosine monophosphate (FCDG) or with FCDG-only control. These mice were then challenged intranasally with an infectious dose of a luminescent strain of B. thailandensis E264 two weeks post-immunization, and correlates of protection were assessed in euthanized mice on days 1, 2, 3, and 7 post-infection. Overall, intranasal vaccination, compared to subcutaneous administration, induced a stronger Th1 (IgG2a/2b) to Th2 (IgG1) antibody response and promoted anti-L1 nasal, pulmonary, and systemic IgA. Additionally, sera IgG from L1-CRM197-vaccinated mice recognized whole-cell B. thailandensis and B. pseudomallei, a select agent exempt strain Bp82. Vaccination ameliorated disease indicators, including luminescent signal and bacterial cell counts, weight and temperature loss, and organ weight, which negatively correlated with IgG2a antibody levels and mucosa-stimulating cytokines IL-13 and IL-9. L1-CRM197-vaccinated mice also had earlier resolution of inflammatory and tissue-damaging cytokines compared to the FCDG-only controls. These results suggest a balanced humoral and cell-mediated response, along with mucosa-This is a provisional file, not the final typeset article based immunity are beneficial for protection. Future efforts should further assess mucosal cellular and humoral mechanisms of protection and test such protection, using aerosolized B. pseudomallei select agent strain(s).